2019
DOI: 10.1007/s12350-018-1359-8
|View full text |Cite
|
Sign up to set email alerts
|

Stomach interference in 82Rb-PET myocardial perfusion imaging

Abstract: Among clinical parameters associated with patient size, BMI was the strongest predictor of MPI interference. Furthermore, a large stomach volume was associated with more severe MPI interference, suggesting that sufficient fasting prior to imminent Rb PET may be important to reduce interference from adjacent radiotracer activity and consequently improve interpretation of MPI results, especially in small patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The paper adds to the prior observation where 200 subjects underwent a clinical 82 Rubidium myocardial perfusion rest/stress PET. 11 A large stomach volume was correlated with significant subdiaphragmatic activity and severe MPI interference. The authors suggested that fasting prior to 82 Rubidium PET MPI may be important to reduce this subdiaphragmatic radiotracer activity.…”
mentioning
confidence: 95%
“…The paper adds to the prior observation where 200 subjects underwent a clinical 82 Rubidium myocardial perfusion rest/stress PET. 11 A large stomach volume was correlated with significant subdiaphragmatic activity and severe MPI interference. The authors suggested that fasting prior to 82 Rubidium PET MPI may be important to reduce this subdiaphragmatic radiotracer activity.…”
mentioning
confidence: 95%
“…In this issue of the Journal of Nuclear Cardiology, Rasmussen et al 16 report their findings on the prevalence of severe interference caused almost exclusively by the stomach on the radiotracer 82 Rb uptake in the LV wall and its inverse association with BMI. They computed the stomach volume by means of delineation of the walls in CT slices and subsequent interpolation to a 3D contour.…”
mentioning
confidence: 99%